Designing a Policy Making Model in Iran' Sport with the Approach of Sport for All Development - Behdad Sadeghi; Rahmatollah Gholipour; Mojtaba Amiri; Marjan Saffari (مدیریت دولتی)
Objective This study was conducted with the goal of designing a policy-making model for sports in Iran, with a focus on the development of 'sport for all'. In terms of purpose, this study is classified as applied research, as it encompasses practical aspects for various organizations related to sports and health, in addition to providing awareness and scientific insights. Furthermore, this research is exploratory in nature, as it aims to design a model on a novel and innovative topic. Methods A mixed qualitative-quantitative method was employed in this study. The qualitative component was conducted using a situation analysis approach, which is one of the methods of grounded theory. The qualitative research involved interviewing experts; thus, 12 experts in the fields of policy making and sport management were interviewed. These experts were either professors or managers of organizations related to sports, possessing over a decade of executive and decision-making experience. Sampling was carried out using targeted and snowball methods. The quantitative section utilized interpretative structural modeling, an approach based on expert opinions, effective for exploring qualitative variables with mutual effects at various levels of importance. Results After an in-depth examination of the interviews and the data obtained, each interview was analyzed individually to extract initial codes. Subsequently, concepts and categories were developed. Messy situational maps, ordered situational maps, and social worlds/arenas maps were identified. The primary categories of the sport policy-making model in Iran for the development of 'sport for all' include contextual factors, mediating factors, role players and influential institutions, executive requirements, environmental complexities, risks, legal problems, external organizational factors, costs and expenses, and interorganizational challenges. With the aid of interpretive structural modeling, conceptual modeling was conducted. Role players and influential institutions emerged as the most significant factors in Iran's sport policy-making process, possessing the highest influence and the least dependence compared to other factors. Conclusion Given that 'sport for all' should be elevated to the level of the country's macro policies, and its development and progress should be approached as a complex issue, the policy for the development of 'sport for all' becomes especially important. Policymakers should give it significant attention. Role players and influential institutions in Iran's sports policy-making process require substantial coordination due to their numerous connections and conflicts. In Iran, 'sport for all' and organized recreation have received limited attention, and currently, there is no mechanism for monitoring sports policies and their continuous implementation. Therefore, it is recommended to implement a national physical activity monitoring plan based on a comprehensive and electronic system. Since the involvement of managers and executives, as well as their cooperation with policymakers in the policy formation process, is crucial, policymakers should be as involved as possible in the implementation process. Additionally, conditions should be facilitated to enable the private sector to effectively engage in this field.